AVALIAÇÃO DAS INTERLEUCINAS IL-6 E IL-10 E QUALIDADE DE VIDA NO CÂNCER DE CÉLULAS ESCAMOSAS ORAL ANTES DA TERAPIA ANTINEOPLÁSICA - Nardi, Daniely Souza de (2021)
Inflammation is responsible for several stages in the process of tumorigenesis, studying pro and antiinflammatory cytokines is important to understand the host's immune response to the establishment of a pathological process such as oral squamous cell cancer. Understanding how this disease affects individuals before antineoplastic therapy and how it can interfere with patients' quality of life is extremely important. the aim of this study is evaluate the expression of the pro and antiinflammatory cytokines IL-6 and IL-10 in patients with oral squamous cell cancer before antineoplastic therapy. The study was carried out at Hospital Universitário Cassiano Antônio Moraes under approval by the Research Ethics Committee (n ° 29.040-091). Thirty-nine patients diagnosed with CCEO by clinical examination were evaluated and flow cytometry analysis of the peripheral blood sample was performed. Epidemiological data were obtained from medical records and quality of life was assessed using the European Organization for Research and Treatment of Cancer Quality of Life-Core 30 questionnaire (eortc qlq-c30). The results show that plasma concentrations of the cytokine IL-6 of the group with CCEO are higher in relation to the control group, as well as the expression in advanced tumor staging III / TIV is high in relation to the initial staging I/II of the disease. Among patients with CCEO, alcohol users had high plasma levels of IL-6 and smokers had higher plasma levels of IL-6 and IL-10. This highlights the role of IL-6 as a marker of tumor progression in patients with CCEO. Patients with increased plasma levels of cytokines showed greater symptoms in terms of loss of appetite, presence of nausea and vomiting, and fatigue (only IL-6) so that we can relate the inflammatory process to the presence of greater symptoms of patients with CCEO.